Year-long implementation of a research-based technology integration professional development coaching model in an elementary school. Issue 4 (2nd September 2020) - Ottenbreit-Leftwich, Anne; Liao, Yin-Chan; Karlin, Michael; Lu, Ya-Huei; Ding, Ai-Chu Elisha; Guo, Meize
Abstract: This multiple case study describes a year-long implementation of a research-based coaching model designed to support changes in elementary teachers' technology integration practices. We examined coaches' perceptions of the model through the use of coaches' questionnaires, reflection notes, and meeting notes. Teachers' coaching experiences were also examined through end-of-year interviews. We identified successes (relationships with teachers, ability to provide personalized support, and teacher change) and challenges (time, technology difficulties, relationships, and collaboration challenges). The primary lessons learned from the coaches' experiences with the research-based PD focused on (1) the impact of personalized support, (2) the relationships between teachers and coaches, and (3) development of the coaches' knowledge.